1987
DOI: 10.1002/ajmg.1320260406
|View full text |Cite
|
Sign up to set email alerts
|

Studies in neural tube defects II. Pathologic findings in a prospectively collected series of anencephalics

Abstract: This report presents the pathologic anatomy of a prospectively collected series of 36 anencephalic infants. This series provides an opportunity to investigate the epidemiology of organ system pathology in anencephaly (AN) as well as other facets of its natural history. AN infants had a mean gestational age 2.5 weeks younger than normal controls, though birthweight was normal for gestational age. Nearly 1/3 of the liveborn infants with AN died within 15 minutes, 2/3 within 3 hours; 3 AN infants survived to 48 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
2

Year Published

1987
1987
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 91 publications
(22 citation statements)
references
References 19 publications
1
19
2
Order By: Relevance
“…This research identified a predominantly young population, which was not significant in other studies (11)(12)(13) . Regarding the duration of pregnancy, preterm birth found in other studies ranged from 50% to 53% meeting the results of this survey, which shows a 55% incidence of this type of delivery.…”
Section: Discussioncontrasting
confidence: 63%
See 3 more Smart Citations
“…This research identified a predominantly young population, which was not significant in other studies (11)(12)(13) . Regarding the duration of pregnancy, preterm birth found in other studies ranged from 50% to 53% meeting the results of this survey, which shows a 55% incidence of this type of delivery.…”
Section: Discussioncontrasting
confidence: 63%
“…Regarding the duration of pregnancy, preterm birth found in other studies ranged from 50% to 53% meeting the results of this survey, which shows a 55% incidence of this type of delivery. The postterm pregnancy had a lower incidence (3.8%) than that observed in other studies, whose numbers ranged between 10% and 17% (11)(12)(13) . Our study also obser ved the occurrence of 6.4% of spontaneous pregnancy loss, which was not found or not observed in other studies.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…Regardless of numbers, the migratory ability of NC cells depends on down-regulation of N-CAM (Thiery et al,, 1982;Bronner-Fraser et al, 1992) and adhesive interactions between themselves and with the 0 1994 WILEY-LISS, INC extracellular matrix (Boucaut et al, 1984;Thiery et al, 1986;Noden, 1988). Craniofacial abnormalities observed with or without an associated neural tube defect may thus be related to altered NC migration into the presumptive facial region during early embryogenesis (Johnston, 1975;Johnston and Bronsky, 1991;Melnick and Myrianthopoulos, 1987). For example, defective NC cell migration from the forebrain neural folds results in frontonasal mesenchyme deficiencies and precludes normal primary palate formation (Johnston, 1975).…”
Section: Introductionmentioning
confidence: 99%